Congenital megalourethra with left ectopic megaureter and bulbar urethral stricture: A rare entity - Kumar, Anil; Roshan, Raj Kishore; Hehr, Rohan; Pandey, Sanjay Kumar; Singh, U S (Eastern Journal of Medical Sciences, 2017)
Congenital megalourethra is a rare disorder of anterior urethra. This disorder is characterized by the congenital absence of corpora spongiosum or cavernosa or both which leads to dilatation of the urethra. We present a case of congenital megalourethra in a 9-month-old child, which was associated with left ectopic megaureter and bulbar urethral stricture. Most of reported cases were treated by Nesbit urethroplasty. This case was initially treated by emergency trocar cystostomy and the left ureteroneocystostomy, and finally, reduction urethroplasty was carried out as a definitive treatment.